Modulatory effects of laurel-leaf cistus (Cistus laurifolius) ethanolic extract on innate immune responses and disease resistance in common carp (Cyprinus carpio) - Bilen, Soner; Mohamed Ali, Gamaia Ali; Amhamed, Iman Daw; Almabrok, Ahmed Alhadi (Elsevier BV, 2021)
Medicinal herbs are used for growth promotion, disease control and other health benefits in aquaculture industry. Here, we examined the effect of dietary laurel-leaf cistus (Cistus laurifolius) ethanolic extract on growth performance, digestive enzyme activity, haematological profile and nonspecific immune responses in common carp (Cyprinus carpio). In addition, resistance against Aeromonas hydrophila infection was examined. Common carp was fed diets containing 0 (Control), 0.1 (CL0.1), 0.5 (CL0.5) and 1 (CL1) g kg-1 laurel-leaf cistus extract for 45 days. After 30 days, superoxide anion production (SAP) increased in CL0.1 and CL0.5 fish groups and at the end of the study all experimental fish groups had higher SAP compared to that of the control (P ˂ 0.05). Lysozyme activity (LA) was elevated in CL0.5 and CL1 treated groups on 30th day (P < 0.05), and this increase was only observed in C0.1 fish group at the end of study compared to control (P ˂ 0.05). Myeloperoxidase activity was significantly increased in CL0.5 and CL1 fish groups at the end of study. IL-1βgene expression was significantly increased in treated fish in a dose-depended manner. Similar results were observed for transcription of IL-6 and IL-8 (P < 0.05). Anti-inflammatory cytokines, IL-10 and TGF-β were highly up-regulated in the intestine and head kidney of CL treated fish groups compared to control (P < 0.05). At the end of experiment, significantly higher final body weight, weight gain, and specific growth rate were obtained in CL0.1 treated fish group compared to control. However, growth was negatively affected in CL1 fish group (P < 0.05). CL1 fish group had also a significantly higher FCR. Amylase activity was significantly increased in all experimental fish groups compared to control (P ˂ 0.05). Trypsin activity was decreased in CL0.1 and CL1 fish groups (P ˂ 0.05). WBC and RBC were significantly increased (P ˂ 0.05) in CL0.5 and CL1 fish groups, whereas haemoglobin, haematocrit, mean cell, mean cell haemoglobin contents were no significantly changed among control and treatment groups. Result of challenge test with A. hydrophila exhibited that survival rate in all treatment groups was significantly higher than that of control. These findings demonstrated that laurel-leaf cistus at 0.1 g kg-1 can be a suitable candidate for growth promotion, immune system induction and infection control in fish.
Keywords: Carps; Ethanol; Plant Extracts; Cistus; Lipase; Head Kidney; Immunity, Innate; Aeromonas hydrophila; Blood Cell Count; Plant Leaves; Fish Diseases; Superoxides; Amylases; Solvents; Animals; Cytokines; Immunologic Factors; Muramidase; Trypsin; Gram-Negative Bacterial Infections; 3. Good health